Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai RSU Kota Tangerang Selatan - Leonitha, Rizka; Ramdani, Danny (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the Influence of Work Discipline and Work Environment on employee performance of RSU Kota Tangerang Selatan. The research method used is a verifiative descriptive method with a quantitative approach. The population in this study amounted to 193 employees and the resulting sample amounted to 130 respondents. The sampling technique is using proportionate stratified random sampling, where sampling is by knowing in advance the number of employees in each division which is then redetermined by sampling for each division at RSU Kota Tangerang Selatan. The analysis tool used is multiple linear regression analysis. The results showed that the picture for Work Discipline, Work Environment and Employee Performance of RSU Kota Tangerang Selatan was considered good. There is a partial influence of Work Discipline on Employee Performance by 34,2%. There is a partial influence of the Work Environment on Employee Performance by 14,4%. There is a simultaneous influence of Work Discipline and Work Environment on employee performance of RSU Kota Tangerang Selatan by 51,3% while the remaining 48,7% is influenced by other variables that were not studied in this study.